IMPOR PARALEL DALAM HUKUM MEREK INDONESIA - Amirul Mohammad Nur (Yuridika, 2015)
Free trade begins with free movement of goods, services, and persons which give chance of importing goods, services, and persons from overseas freely come to Indonesia. Genuine importation in the same goods in a different markets region, will creating it’s own market. The differences of jurisdiction territory and barriers to entry will give opportunity to market participants selling their imports products competitively. Parallel Importation occur when importers bring their genuine products, together with the Licensee (license holder) selling their genuine products competitively-cheaper, in the same time (parallel), with the selling genuine product by Trademark Owner. Trademark protection have important roles on parallel importation, good comprehension of Trademark exploration rights and protection for related parties will avert market participants from business loss. For law enforcement authorities also able to resolve parallel import disputes in a fair way and truly based on Trademark Law.